2007
DOI: 10.1002/ca.20509
|View full text |Cite
|
Sign up to set email alerts
|

Epineurial compartments and their role in intraneural ganglion cyst propagation: An experimental study

Abstract: New patterns of intraneural ganglion cyst formation are emerging that have not previously been explained in current pathoanatomic terms. We believe there are three important elements underlying the appearance of these cysts: (a) an articular branch of the nerve that connects to a nearby synovial joint; (b) ejected synovial fluid following the path of least resistance along tissue planes; and (c) the additional effects of pressure and pressure fluxes. The dynamic nature of cyst formation has become clearly appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…First confronted by an unexplained clinical outlier in the literature from the pre-MRI (magnetic resonance imaging) era (Jacobs et al, 1975), then puzzled by the MRIs in several of our own patients with multiple intraneural ganglion cysts within sciatic, tibial, fibular, and sural nerves which were all derived from a single joint of origin (i.e., the superior tibiofibular joint), we put forth an anatomic explanation for this new pattern and concept (Spinner et al, 2007a,c): cyst fluid ascending up the primarily ''affected'' nerve could reach the level of the sciatic nerve, fill its common epineurial sheath and spread circumferentially (cross over), at which time pressure fluxes could result in further ascent up the sciatic, descent down the same parent nerve or one of its branches (i.e., the sural), or descent down the opposite, previously ''unaffected'' fibular or tibial nerves. We then confirmed the phenomenon of cross-over and bidirectional flow in an experimental model using selective dye injections (Spinner et al, 2007d).…”
Section: Introductionsupporting
confidence: 64%
“…First confronted by an unexplained clinical outlier in the literature from the pre-MRI (magnetic resonance imaging) era (Jacobs et al, 1975), then puzzled by the MRIs in several of our own patients with multiple intraneural ganglion cysts within sciatic, tibial, fibular, and sural nerves which were all derived from a single joint of origin (i.e., the superior tibiofibular joint), we put forth an anatomic explanation for this new pattern and concept (Spinner et al, 2007a,c): cyst fluid ascending up the primarily ''affected'' nerve could reach the level of the sciatic nerve, fill its common epineurial sheath and spread circumferentially (cross over), at which time pressure fluxes could result in further ascent up the sciatic, descent down the same parent nerve or one of its branches (i.e., the sural), or descent down the opposite, previously ''unaffected'' fibular or tibial nerves. We then confirmed the phenomenon of cross-over and bidirectional flow in an experimental model using selective dye injections (Spinner et al, 2007d).…”
Section: Introductionsupporting
confidence: 64%
“…In dye studies, injection of the outer epineurium allows observation of primary ascent, sciatic cross-over, and terminal branch descent in an experimental model and a barrier between the outer and inner epineuria. 37,41 We invoke these anatomically relevant data to draw a clinical corollary. We have identified three sequential phases of peroneal and tibial intraneural ganglia cyst formation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the articular theory has been the most widely accepted. According to the articular theory, INGCs are formed as the joint fluid under pressure passes through the capsular defect and propagates along the articular branch of the nerve . Joint fluid dissects proximally up the articular branch within the epineurium along the path of least resistance …”
Section: Discussionmentioning
confidence: 99%
“…Spinner et al found that dye injected in the outer epineurium remained in the outer epineurium, whereas dye injected in the inner epineurium crossed over to the adjacent nerve fascicle . In addition, it was suggested that sciatic crossover between tibial and common peroneal nerve occurs when INGCs spread along the outer as opposed to inner epineurium.…”
Section: Discussionmentioning
confidence: 99%